2012
DOI: 10.1186/1471-2202-13-141
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal diffusion tensor imaging in amyotrophic lateral sclerosis

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder, caused by progressive loss of motor neurons. Changes are widespread in the subcortical white matter in ALS. Diffusion tensor imaging (DTI) detects pathological changes in white matter fibres in vivo, based on alterations in the degree (diffusivity, ADC) and directedness (fractional anisotropy, FA) of proton movement.Methods24 patients with ALS and 24 age-matched controls received 1.5T DTI. FA and ADC were analyzed using statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 40 publications
9
87
2
5
Order By: Relevance
“…Previous studies comparing musicians with nonmusicians yielded contradictory results with regard to FA values in corticospinal motor tracts, and none of the studies related diffusivity measures to motor performance measures (Schmithorst and Wilke 2002;Bengtsson et al 2005;Han et al 2009;Imfeld et al 2009). Studies examining neural effects of long-term instrumental music practice have been complemented by studies showing white matter plasticity in response to the acquisition of other nonmusical sensorimotor skills (Scholz et al 2009;Hanggi et al 2010;Landi et al 2011) as well as in response to recovery from neurological disorders (Schlaug et al 2009;Wrigley et al 2009;Lindenberg et al 2010;Granziera et al 2012;Keil et al 2012;Zipse et al 2012) or neural effects of immobilization (Langer et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing musicians with nonmusicians yielded contradictory results with regard to FA values in corticospinal motor tracts, and none of the studies related diffusivity measures to motor performance measures (Schmithorst and Wilke 2002;Bengtsson et al 2005;Han et al 2009;Imfeld et al 2009). Studies examining neural effects of long-term instrumental music practice have been complemented by studies showing white matter plasticity in response to the acquisition of other nonmusical sensorimotor skills (Scholz et al 2009;Hanggi et al 2010;Landi et al 2011) as well as in response to recovery from neurological disorders (Schlaug et al 2009;Wrigley et al 2009;Lindenberg et al 2010;Granziera et al 2012;Keil et al 2012;Zipse et al 2012) or neural effects of immobilization (Langer et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Previous DTI studies using an ROI method showed a bilateral reduction in FA along the CST (Jacob, Finsterbusch et al 2003) while other studies found changes in CST to be confined to the right hemisphere (Zhang, Schuff et al 2011). The changes in motor pathways over time are consistent with the known atrophy in ALS (Jacob, Finsterbusch et al 2003, Keil, Prell et al 2012). …”
Section: Discussionmentioning
confidence: 52%
“…MRI gives an insight in the understanding of disease pathology and the possible progression of disease to other body regions (Keil, Prell et al 2012). Since MRI is a non-invasive imaging technique, it has been extensively applied in neuroscience and neurological diseases and has the potential to be a useful biomarker for progression of ALS.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations